2020
DOI: 10.3390/microorganisms8071093
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Antimicrobial Compounds from Food and Marine-Sourced Carnobacterium Species through Phenotype and Genome Analyses

Abstract: Carnobacterium maltaromaticum and Carnobacterium divergens, isolated from food products, are lactic acid bacteria known to produce active and efficient bacteriocins. Other species, particularly those originating from marine sources, are less studied. The aim of the study is to select promising strains with antimicrobial potential by combining genomic and phenotypic approaches on large datasets comprising 12 Carnobacterium species. The biosynthetic gene cluster (BGCs) diversity of 39 publicly available Carnobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
2
9
0
Order By: Relevance
“…Kinetics of C. maltaromaticum 3 Ba‐2‐II H 2 O 2 production was compared to a Lactococcus garvieae freshwater isolate (this study), a species known to produce inhibitory amounts of H 2 O 2 (Delpech et al, 2017). Cultures were grown in Erlenmeyer flasks with 20 mL ATP medium, at 25°C with 150‐rpm shaking and OD600 nm for 24 h. H 2 O 2 concentration was measured at 2‐h intervals using Dosatest® Peroxide test strips (VWR, Fontenay‐sous‐Bois, France) (Begrem et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetics of C. maltaromaticum 3 Ba‐2‐II H 2 O 2 production was compared to a Lactococcus garvieae freshwater isolate (this study), a species known to produce inhibitory amounts of H 2 O 2 (Delpech et al, 2017). Cultures were grown in Erlenmeyer flasks with 20 mL ATP medium, at 25°C with 150‐rpm shaking and OD600 nm for 24 h. H 2 O 2 concentration was measured at 2‐h intervals using Dosatest® Peroxide test strips (VWR, Fontenay‐sous‐Bois, France) (Begrem et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Genome annotation was performed using Prokka v. 1.13 (Seemann, 2014) and RAST (Aziz et al, 2008;Brettin et al, 2015;Overbeek et al, 2014). The presence of genes encoding the production of antimicrobial compounds was probed with query sequences from Begrem et al (2020) and UniProt (https://www.uniprot. org/), as well as by AntiSMASH 6.0 (Blin et al, 2021) andBAGEL 4 (van Heel et al, 2018).…”
Section: Genomic Analysesmentioning
confidence: 99%
“…Antimicrobial activities of probiotic strains were assessed using a miniaturized spot-on-lawn method as previously described ( Begrem et al, 2020 ). Briefly, 10 μl of 24 h-probiotic strain cultures were spotted onto soft agar plates inoculated with one of 24 target strains involved in fish diseases, human infections or seafood spoilage ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Comparative genomics of Carnobacterium highlighted potential new candidate strains for biopreservation, efficient against L. monocytogenes and harbouring original bacteriocin gene equipment. For example, five different bacteriocins and a 16 kDa new one were predicted in the C. maltaromaticum SF668 and C. maltaromaticum EBP3019 genomes, respectively ( Begrem et al, 2020 ). Combining genome analysis and peptidomics of a Companilactobacillus crustorum strain enabled, from the peptides produced during the growth of this strain, the discovery of eight novel bacteriocins and two other antimicrobials with a broad spectrum of action against Gram-positive and Gram-negative pathogens ( Yi et al, 2018 ).…”
Section: Selection Of Biopreservation Agentsmentioning
confidence: 99%
“…Such molecules may have antimicrobial functions or be associated with oxidative stress resistance, and immunomodulatory or cytotoxicity activities. Comparative genomic analysis of Carnobacterium strains showed that this PKS/NRPS gene cluster is unique in C. divergens V41 ( Begrem et al, 2020 ). Other PKs/NRPs antimicrobial compounds, such as milkisin produced by a Pseudomonas sp.…”
Section: Selection Of Biopreservation Agentsmentioning
confidence: 99%